Pengembangan Sistem Informasi Manajemen Mobil Unit Donor Darah (Studi Kasus : Palang Merah Indonesia (PMI) Kota Malang) - Mochammad Ali Hafidz; Satrio Agung Wicaksono; Adam Hendra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The Indonesian Red Cross (PMI) Malang is a national association organization in Indonesia engaged in social humanity where one of its main tasks is to provide blood transfusion service to the community. One way PMI to get blood is through the car blood donation unit by cooperate with agencies or organizations. The problems that arise is take 3-5 days to make the registration process until the date of agreement and reporting activities are still done manually. Based on the problems that have been explained, it developed a Management Information System Car Blood Donation Unit that aim to improve the process of registration car units for organizers candidate and simplify the report of activities car blood donation unit at PMI Malang. The development of this system was built using waterfall method and implemented on the website. The developed system has 16 functional requirements, 1 non functional requirement to support business process at PMI Malang City. Black box test results obtained results of 100% valid. At the time comparison test, the result of decreasing the registration time of the unit car is 98.5% from the previous registration time. In the User Acceptance Testing test given to the organizers generate revenue by 90%, the donor management division is 80%, the unit car officer is 80%, and the head of the utd is 80%.